A novel transpalatal‐transoral robotic surgery approach to clival chordomas extending into the nasopharynx. Issue 8 (10th April 2019) - Henry, Laura E.; Haugen, Thorsen W.; Rassekh, Christopher H.; Adappa, Nithin D.; Weinstein, Gregory S.; O'Malley, Bert W.
Abstract: Background: In this paper, we present three cases where a novel transoral robotic surgery (TORS) approach was used to resect clival chordomas extending into the nasopharynx to demonstrate progress in the evolution of robotic surgery of the head and neck. Methods: The first patient had a history of metastatic chordoma resection and presented with trismus and dysphagia; the second and third patients had first presentation with nasal congestion and facial numbness, respectively. All patients underwent a novel transpalatal‐TORS resection. Results: Total resection was achieved in the first patient and near‐total resections were achieved in the second and third patients. All patients had minimal postoperative morbidity and no patients experienced significant adverse events. Conclusion: Clival chordomas are rare, potentially dangerous lesions with a high rate of recurrence. The novel transpalatal‐TORS approach to these tumors presented in this series represents advancement in the realm of minimally invasive surgery of the head and neck. This approach offers patients total or near‐total control of these lesions with minimal intraoperative and postoperative side effects.